MENINGKATKAN PARTISIPASI PEMILU PEMULA DALAM PILKADA GUBERNUR DAN WALI KOTA TAHUN 2024 DI SMAS AL ULUM MEDAN - Husna, M. Faisal; rozi, Fachrurozi; Tarigan, M. Egya Farhan (Cattleya Darmaya Fortuna, 2025)
This article discusses efforts to increase the participation of first-time voters in the 2024 Regional Head Election (Pilkada) for Governor and Mayor at SMA Al Ulum Medan. With the high rate of abstention among young voters, this article aims to analyze the factors that influence the low participation of first-time voters and identify steps that can be taken to increase their awareness and involvement in the electoral process. Through a participatory approach involving political education in schools, outreach, and the use of social media, this article proposes relevant strategies to optimize the participation of first-time voters in the upcoming regional elections. It is hoped that the results of this research can make a positive contribution to improving the quality of democracy in Indonesia, especially among the younger generation.